PENDAMPINGAN PENDIDIKAN SEKSUALITAS MELALUI KITAB TARBIYATUL AULAD PADA MAHASISWA SATGAS PPKS DI JOMBANG - Rofi'ah, Siti; Jasminto; Kibtiyah, Asriana; Mahsun, Ali; Bahrodin, Ariga; Muslih, Imam; Andeastya, Vian Hanes (ABIDUMASY, 2024)
Sexual education is an important aspect in efforts to prevent sexual violence inhigher education. However, the understanding of sexual education is often limited and notintegrated with Islamic values. This research aims to assist PPKS Task Force students inunderstanding sexual education through an approach based on the book Tarbiyatul Aulad byAbdullah Nasih Ulwan. This approach emphasizes Islamic values that are moderate, balanced,and relevant to the current context. This mentoring activity uses a participatory approachwhich includes the preparation stage, introduction stage, deepening stage, implementationstage and reflection evaluation stage. The results of the activity show that the Task Forcestudents' understanding of sexual violence and sexual education has increased. increasedunderstanding of the concept of Islamic-based sexual education and understanding of the issueof sexual violence. The integration of Islamic values in sexual education through the Book ofTarbiyatul Uulad has a positive impact on strengthening the capacity of PPKS Task Forcestudents in Higher Education.